The Evaluation of Mustahiq Empowerment-Based Poverty Alleviation Program at Amil-Zakat Organizations - Fikriyah, Khusnul; Ridlwan, Ahmad Ajib (International Journal of Islamic Business and Economics (IJIBEC), 2018)
The increasing number of the poor in Indonesia makes the management of zakat play more important role. LAZs (non-profit organizations managing zakat) which functions as collecting and distributing zakat, infaq, and shadaqah in Indonesia is potential to develop as an attempt for equal distribution of national income, as well as a solution for poverty alleviation. Common empowerment programs by LAZs include education, health, social-humanity, and economy. Those all are consistent with government’s poverty alleviation programs, as mentioned in the Constitution 1945. “Evaluation of Mustahiq Empowerment-Based Poverty Alleviation Program at Amil-Zakat Organizations in Surabaya” points to a theory by Wirawan that evaluation was conducted through three phases; evaluation of process, evaluation of usage, and evaluation of effect. it aims to see whether or not LAZs’ empowerment programs run well and thus, be potential to be developed as a solution for poverty in Indonesia. The result showed that the empowerment programs in education and health areas were found well-implemented, while the other facets including economy and social-humanity still need more improvement within.